2020
DOI: 10.1097/sla.0000000000003093
|View full text |Cite
|
Sign up to set email alerts
|

Oea Signaling Pathways and the Metabolic Benefits of Vertical Sleeve Gastrectomy

Abstract: Objective: The aim of this study was to determine whether downstream [peroxisome proliferator-activated-receptor alpha (PPARα) and the G-protein coupled receptor, GPR119] and upstream (a fatty acid translocase, CD36) signaling targets of N-oleoylethanolamide (OEA) were necessary for weight loss, metabolic improvements, and diet preference following vertical sleeve gastrectomy (VSG). Summary Background Data: OEA is an anorectic N-acylethanolamine produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…VSG mice also had improved oral glucose tolerance compared with sham surgery mice (Figure 1F). These data highlight that we have replicated our previous findings regarding the impact of VSG on BW, food intake, and glucose tolerance (19)(20)(21).…”
Section: Resultssupporting
confidence: 89%
“…VSG mice also had improved oral glucose tolerance compared with sham surgery mice (Figure 1F). These data highlight that we have replicated our previous findings regarding the impact of VSG on BW, food intake, and glucose tolerance (19)(20)(21).…”
Section: Resultssupporting
confidence: 89%
“…Intestinal GLP-1 is not necessary for the glycemic improvements after VSG. VSG produces reliable 3-to 4-fold increases in postprandial plasma GLP-1 levels in mice (26,27). We hypothesized that this large increase in postprandial GLP-1 comes from the intestine and that the degree of the increase would lead to a more prominent role for this source of GLP-1 in regulating glucose tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Moran et al found that the gastric inhibitory effect produced by OEA may involve pancreatic polypeptide (PPY) [ 50 ]. OEA can trigger effects similar to those observed after bariatric surgery, including reduced food intake, reduced fat mass, increased GLP-1 release, and reduced lipid levels, which are undoubtedly beneficial to patients with MAFLD [ 69 ].…”
Section: Introductionmentioning
confidence: 99%